SQUEEZED-LIGHT GENERATION IN SEMICONDUCTORS - Fox, A; Baumberg, J; Dabbicco, M; Huttner, B; Ryan, J (1995)
We have generated pulsed squeezed light using the third-order nonlinear susceptibility of the semiconductor ZnS at room temperature. The photon energy was chosen to be below midgap in order to minimize nonlinear absorption. Efficient quadrature squeezing of 2.2 dB (40%) was obtained using 125 fs pulses at a center wavelength of 780 nm. The measured noise is suppressed below the quantum limit over the entire range of our detection bandwidth (30-50 MHz). The scheme employed can generally be applied to semiconductors, and opens the way for squeezed light generation over a wide range of wavelengths.